Vedic Beliefs on Environment and Sustainable Development - Kalauni, Mukund Ballabh (Journal of Development and Social Engineering, 2023)
Sustainable development means creating an environment that is necessary for humans without disturbing the nature. The concept of sustainable development emerged when in the name of progress nature was being destroyed, often neglecting the wisdom passed down from our ancestors. The objective of this research paper is to explain the Vedic knowledge in the context of the sustainable development as a modern concept and to find the facts related to environment and development. The research is qualitatively designed using available secondary sources of information and knowledge of Vedas, Upanishads, Purans and Niti Sholkas related to environment and sustainable development. To make it more informative, interviews were carried out with key informants as primary sources of data. As mentioned in the Atharvaved, earth is assumed as mother and all creatures are her children, which showed the positive attitude of environment protection. The emphasis on the purity and protection of river, jungle and air needs to be revived and only then the concept of sustainable development can be meaningful. Vedic literature will be much useful to understand the concept of development in a comprehensive way. It is notable fact that the earth is useful for humans as well as for all creatures of the world and for the whole universe. Only the way to protect the universe from tensions, pollutions, war and conflicts is Vedic concept that regards the universe as a family. Only by incorporating Vedic knowledge into the concept of modern development can we meet the standards of sustainable development.